Absence of ECG Task Force Criteria does not rule out structural changes in genotype positive ARVC patients. (15th October 2020) - Stokke, Mathis K.; Castrini, Anna I.; Aneq, Meriam Åström; Jensen, Henrik Kjærulf; Madsen, Trine; Hansen, Jim; Bundgaard, Henning; Gilljam, Thomas; Platonov, Pyotr G.; Svendsen, Jesper Hastrup; Edvardsen, Thor; Haugaa, Kristina H.
Abstract: Aims: In Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC), electrophysiological pathology has been claimed to precede morphological and functional pathology. Accordingly, an ECG without ARVC markers should be rare in ARVC patients with pathology identified by cardiac imaging. We quantified the prevalence of ARVC patients with evidence of structural disease, yet without ECG Task Force Criteria (TFC). Methods and results: We included 182 probands and family members with ARVC-associated mutations (40 ± 17 years, 50% women, 73% PKP2 mutations) from the Nordic ARVC Registry in a cross-sectional analysis. For echocardiography and cardiac MR (CMR), we differentiated between "abnormalities" and TFC. "Abnormalities" were defined as RV functional or structural measures outside TFC reference values, without combinations required to fulfill TFC. ECG TFC were used as defined, as these are not composite parameters. We found that only 4% of patients with ARVC fulfilled echocardiographic TFC without any ECG TFC. However, importantly, 38% of patients had imaging abnormalities without any ECG TFC. These results were supported by CMR data from a subset of 51 patients: 16% fulfilled CMR TFC without fulfilling ECG TFC, while 24% had CMR abnormalities without any ECG TFC. In a multivariate analysis, echocardiographic TFC were associated with arrhythmic events. Conclusion: More than one third of ARVC genotype positive patients had subtle imaging abnormalities without fulfilling ECG TFC. Although most patients will have both imaging and ECG abnormalities, structural abnormalities in ARVC genotype positive patients cannot be ruled out by the absence of ECG TFC. Graphical abstract: Unlabelled Image Highlights: The study included data from 182 patients and relatives in the Nordic ARVC Registry. We analyzed prevelances of abnormalities in ECG, echocardiography and CMR. More than one third of patients had imaging abnormalities without ECG TFC. The prevalence of abnormalities strongly depended on criteria used. Structural changes in ARVC cannot be ruled out by the absence of ECG TFC.